Analysis of power output time series in response to supramaximal exercise: An approach through dynamic factor analysis - Bruno, P. M.; Duarte Pereira, F.; Fernandes, R.; Vilhena de Mendonca, G. (Pediatric Exercise Science, 2011)
The responses to supramaximal exercise testing have been traditionally analyzed by means of standard parametric and nonparametric statistics. Unfortunately, these statistical approaches do not allow insight into the pattern of variation of a given parameter over time. The purpose of this study was to determine if the application of dynamic factor analysis (DFA) allowed discriminating different patterns of power output (PO), during supramaximal exercise, in two groups of children engaged in competitive sports: swimmers and soccer players. Data derived from Wingate testing were used in this study. Analyses were performed on epochs (30 s) of upper and lower body PO obtained from twenty two healthy boys (11 swimmers and 11 soccer players) age 11-12 years old. DFA revealed two distinct patterns of PO during Wingate. Swimmers tended to attain their peak PO (upper and lower body) earlier than soccer players. As importantly, DFA showed that children with a given pattern of upper body PO tend to perform similarly during lower body exercise.